Barreiras no interesse pelo dispositivo intrauterino (DIU) na atenção primária à saúde - Nogueira, Camila Sampaio (2024)
Introduction: Currently, there is still a lack of knowledge about the Intrauterine Device (IUD), taboos about it, insecurities and some afflictions among those interested in the method, which often leads to discouragement in seeking the IUD as a form of contraception. Aim: To identify, in a Primary Health Care setting, possible factors associated with seeking the IUD as a contraceptive method and their influence on women's reproductive and sexual health. Methodology: A cross-sectional study, with a descriptive-quantitative approach, carried out in two Primary Health Care Units (UAPS), located in one of the Metropolitan Regions of Fortaleza, in Caucaia, by means of an interview based on the application of a supervised questionnaire with open and closed questions, by two trained interviewers, to women in the reproductive period awaiting elective consultations or spontaneous demand, under consent, making up a consecutive, non-probabilistic sample, from December 2022 to June 2024. The data was collected and analyzed on the RedCap® platform using the Kolmogorov-Smirnov normality test and the Mann-Whitney test. Results: 173 women were interviewed, most of whom were brown (69.9%), had children (73.3%), were married/stable (60.1%) and had completed high school (50.3%). Most of the women reported that there were factors discouraging them from seeking the IUD as a contraceptive method, the most common being lack of information about the method and fear. There was an association (p<0.001) between lack of information and lack of interest in the device. Conclusion: Among the barriers to interest in the IUD in PHC, poor information to patients at an opportune moment in health care is an important gap to be resolved. Health education is part of the process of empowering women, and it is also the right of users to have access to this information, allowing them to choose their method individually, according to their expectations and health condition.